Evaluative Design of Strategic Management Implementation at Regencies and Cities Development - Suprijadi, Bambang (Jurnal Aplikasi Manajemen, 2012)
Decentralization era makes change the design of development strategic management at local government. Local autonomy assert that planning authority is on local government's hand. The local election makes the political campaign at the city mayor/regent as the refence point of RPJMD. The design change demands strict, effective and efficient evaluation process. The study designs the general evaluation of strategic management implementation at regencies and cities level. The study used ex post and ex ante models simulations. The study observs various law regulations about evaluations and refide former evaluation models weaknesses.As the results, the study recommends that the strategic management evaluation should be done in evaluation types, that is SKPD local government task force evaluation on its capacity in implementing the middle term development plan and SKPD capacity evaluation in implementation. Evaluation realization is condised by measuring the consistence and achievement the target indicator from: (i)activities (output), (ii) program (outcome), and (iii) objectives (impacts): While, the SKPD capacity evaluation is done by (i) using 24 key indicators (ii) based on AHP method to determine indicator weight (iii) evaluators consist of superiors, SKPD partner, subordinate UPT and themselves, and (iv) FGD utilization aims to determine each evaluator weight. To reach high efficiency, evaluation process should be done since the beginning when city mayor/regent starts their official position.